(untitled) (Journal of Nepal Physical Society, 2017)
Heusler alloys have been of great interest because of their application in the field of modern technological applications. Electronic and magnetic properties of Co, Mn, Si and the Heusler alloy Co2MnSi have been studied using Density functional theory based Tight Binding Linear Muffin Tin Orbital with Atomic Sphere Approximation (TB-LMTO-ASA) approach. From the calculation lattice parameter of optimized structure of Co, Mn, Si and Co2MnSi are found to be 2.52Å, 3.49Å, 5.50Å, 5.53Å respectively. Band structure calculations show that Co and Mn are metallic, Si as semi-conducting while the Heusler alloy Co2MnSi as half-metallic in nature with band gap 0.29eV. The charge density plot indicates major bonds in Co2MnSi are ionic in nature. Magnetic property has been studied using the density of states (DOS), indicating that Co and Co2MnSi are magnetic with magnetic moments 2.85μB and 4.91μB respectively. The contribution of orbital in band structure, DOS and magnetic moments are due to d-orbital of Co and Mn and little from s and p-orbital of Si in Co2MnSi alloy. Journal of Nepal Physical Society Volume 4, Issue 1, February 2017, Page: 60-66